"Forget about the words"? Tracking the language, media and semiotic ideologies of digital discourse: The case of sexting. (December 2017) - Thurlow, Crispin
Abstract: This paper considers how the social meanings of digital discourse are metadiscursively framed and structured by a combination of language, media and semiotic ideologies; that is, culturally shared beliefs about how words, technologies and meaning-making work. Illustrated with examples drawn from news-media stories and other mediatized texts, I demonstrate what this looks like in practice through a three-part, multimodal analysis of "sexting" as a case in point. Grounded first in the linguistic and visual accomplishment of three familiar language-ideological strategies (i.e. iconization, erasure, recursivity ), my analysis is then expanded to incorporate four closely related media-ideological issues ( materiality, authorship, remediation, historicity ) before turning to mode / modality and performativity as two key instantiations of semiotic ideology. While digital discourse studies should certainly not "forget about the words", it needs always to stay attentive to the complex intersection of language with media and semiotic ideologies. This analytical principle has particular importance for critically-oriented work concerned with the way digital media are used to discipline, for example, sex and sexuality.